Public Opinion Sentiment Analysis on the Indonesian Music Royalty Polemic in the Public Space using the RoBERTa Transformer: A Case Study of YouTube Comments - Irman, Dede; Surya, Dhika; Laksitohika, Grida Saktian (Communication in Research and Publications (CRP), 2025)
This study aims to analyze public perception of the music royalty controversy in Indonesia through YouTube comments. The development of digital technology has made YouTube a public space where discourse on cultural and policy issues, such as music royalty payments in the commercial space, is openly expressed. This study uses a quantitative approach with sentiment analysis based on the RoBERTa (Robustly Optimized BERT Pretraining Approach) model adapted for Indonesian, namely the Indonesian RoBERTa Base Sentiment Classifier. Primary data was obtained from comments on a YouTube video titled